PRINSIP KEHATI-HATIAN DALAM BISNIS KARTU KREDIT PADA PT. BANK NEGARA INDONESIA SENTRA BISNIS KARTU MEDAN - Liza Bayduri Nasution; Tan Kamello; Dedi Harianto; Utary Maharani Barus (Universitas Sumatera Utara, 2015)
ABSTRACT Credit card is one of products issued by banks. In credit card processing should be precautionary principles in order to the using of credit card does not emerge, which cause the loss foward the banks issuing credit card and the card holders. The problem of this study, such as How does PT.BNI Card Business Centre apply the precautionary principles in accordance of the internal rules of credit card business handling? What are the form of violation of the precautionary principles in the credit card busines activities? How does the accounttability related to credit card business and the accomplishment of problem loans? Precautionary principles are applied in the credit card application process. The terms of the precautionary principle violation in credit card business activities may accur the time of the documents of the card applicant are not actually checked. In case of violation of precautionary principles occured by internal party the officer,concerned,sould be responsible for the violation. Keywords: Prudential Principle, Credit Card, Banking Regulation